Pulmonary sclerosing pneumocytoma masquerading as lung metastasis - Mi Young Kim; Hee Yong Kwak; Hojung Lee; Man Sil Park (Medicine, 2026)
Rationale: Pulmonary sclerosing pneumocytoma (PSP) is a rare benign neoplasm primarily affecting middle-aged Asian women. Although typically presenting as a well-circumscribed solitary nodule with an indolent clinical course, PSP can occasionally exhibit aggressive radiological features. In patients with a history of malignancy, these atypical findings can lead to a significant diagnostic dilemma, frequently mimicking metastatic disease. Patient concerns: A 42-year-old female with a history of breast cancer was referred for evaluation of a lung nodule identified during surveillance. Contrast-enhanced chest computed tomography (CT) revealed a 1.6-cm juxtapleural mass in the right middle lobe. Notably, the lesion showed apparent vessel abutment and suspected vascular invasion, leading to a presumptive radiological diagnosis of angioinvasive metastasis. F-fluorodeoxyglucose positron emission tomography/CT demonstrated low F-fluorodeoxyglucose uptake with a maximum standardized uptake value of 1.6. Diagnoses: Despite the preoperative suspicion of malignancy based on aggressive CT features, the diagnosis of PSP was confirmed through histopathological examination following surgical intervention. Interventions: The patient underwent an open wedge resection. Intraoperative findings revealed a well-demarcated mass without inflammatory adhesions or pericardial involvement. Outcomes: The postoperative course was uneventful, and no recurrence was observed during the follow-up period. Lessons: This case highlights that PSP can radiologically masquerade as angioinvasive metastasis, especially in oncological patients. Clinicians and radiologists should consider PSP as a differential diagnosis for solitary pulmonary nodules with suspected vascular invasion, even when positron emission tomography/CT shows low metabolic activity. Histopathological confirmation remains the gold standard for avoiding overdiagnosis and unnecessary radical treatment.